Formulasi dan uji aktivitas sediaan lotion tabir surya ekstrak etanol 96% bekatul beras merah (Oryza nivara) - Listiani, Putu Ayu Ratih; Indraswari, Putu Ika Indah; Ferrandani, Ni Putu (Sasambo Journal of Pharmacy, 2023)
Brown Rice Bran (Oryza nivara) contains phenolic compounds, flavonoids, tannins, steroids, or terpenoids that can function as an antioxidant activity that can protect the skin from the adverse effects of UV rays of the sun. Extraction was carried out by maceration method using 96% ethanol as solvent. The viscous extract obtained was then subjected to phytochemical screening and SPF test and made into three different concentrations, 5%, 10%, and 15%, which would then be formulated into a sunscreen lotion dosage form. The resulting preparations evaluated the physical quality of lotion preparations in the form of organoleptic tests, homogeneity tests, pH tests, dispersibility tests, and SPF tests of preparations. The results of the SPF test extract with concentrations of 5%, 10%, and 15% showed that the protection produced was in the ultra-category with SPF values respectively 31.1, 40.1, and 45.1. The results of the physical evaluation of the preparation of sunscreen lotion with brown rice bran extract showed that the lotion produced was not homogeneous, and the results of the pH test and dispersion test still met the requirements. Testing the SPF value of lotion preparations showed that the protection produced by each formula was in the maximum to ultra-category with SPF values of 11.7, 14.1, and 16.4, respectively.